2021
DOI: 10.1158/1078-0432.ccr-20-2782
|View full text |Cite
|
Sign up to set email alerts
|

The Oxford Classic Links Epithelial-to-Mesenchymal Transition to Immunosuppression in Poor Prognosis Ovarian Cancers

Abstract: Serous ovarian cancer is the most common histological subtype of ovarian carcinoma. Due to substantial genetic heterogeneity, it has been challenging to develop robust prognostic classifications based on molecular stratification of high-grade serous ovarian cancer. We recently defined a gene panel "the OxC" that robustly identifies a poor prognosis EMT-high subtype of HGSOC. Here we demonstrate that the NanoString-based OxC-derived high EMT scores are associated with poor prognosis in ovarian cancer independen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…To test this assumption, we next quantified the EMT cell state in the OXO-PCR samples using our recently described deconvolution-based classifier ( 22 , 23 ). This analysis revealed that MRD cells are particularly enriched in genes belonging to the EMT signature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test this assumption, we next quantified the EMT cell state in the OXO-PCR samples using our recently described deconvolution-based classifier ( 22 , 23 ). This analysis revealed that MRD cells are particularly enriched in genes belonging to the EMT signature.…”
Section: Resultsmentioning
confidence: 99%
“…To test these alternatives, we compared the adipocyte-like gene signature between EMT-high and EMT-low prechemotherapy tumors using publicly available data sets of prechemotherapy HGSOC, TCGA ( 12 ), and the Australian Ovarian Cancer Study (AOCS) ( 24 ). We divided the samples according to our previously described EMT score ( 22 , 23 ) into EMT-high and EMT-low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the spatial analysis of the TME revealed significant stromalto-stromal metacluster spatial interactions in the HRwt tumors, suggesting the presence of physical and biochemical barriers which can further promote therapy resistance 14,23,24 . Moreover, we found that the HRwt tumors contained an increased proportion of tumor cells with an EMT phenotype without tumor-immune spatial interactions, which also could contribute to chemoresistance [25][26][27] . Altogether, the stromal dominance, tumor cell EMT functional states, and decreased immune surveillance can contribute to the poor prognosis of the HRwt tumors.…”
Section: Spatial Cell-cell Interactions Suggest Enhanced Immunosurveimentioning
confidence: 86%
“…TWIST1 was suggested to be a regulator of EOC stemness through controlling stem cell differentiation via regulation of miR-199a and miR-214 [31][32][33] . Furthermore, increased TWIST1 expression in CSCs has been shown to promote their differentiation into mesenchymal cells with CSC-like properties and capacity for migration [32,34] . Profiling of HGSOC tumors using the Oxford Classic classifier for molecular stratification of tumors demonstrated that EMT-high tumors were associated with poor survival and linked to immunosuppression [35] .…”
Section: Introductionmentioning
confidence: 99%